(untitled) (Swiss Medical Weekly, 2023)
BACKGROUND: Animal and human bite injuries are a relevant health problem worldwide. With the increasing number of pets, bite injuries are becoming more frequent. Previous studies on animal and human bite injuries in Switzerland were completed several years ago. The aim of the present study was to provide a detailed overview of patients with bite injuries admitted to a tertiary emergency department in Switzerland in terms of demographics, injury patterns and treatment strategies. METHODS: A 9-year cross-sectional analysis of patients presenting to the emergency department of Bern University Hospital in the period January 2013 to December 2021 following an animal or human bite injury. RESULTS: A total of 829 patients with bite injuries were identified, including 70 for postexposure prophylaxis only. Their median age was 39 (IQR 27–54) years and 53.6% were female. Most patients were bitten by a dog (44.3%), followed by cats (31.5%) and humans (15.2%). Most bite injuries were mild (80.2%); severe injuries were mainly found in dog bites (28.3%). Most patients were treated within six hours after human (80.9%) or dog (61.6%) bites; after cat bites, patients often presented with a delay (74.5%) and signs of infection (73.6%). Human bite wounds were superficial in the majority of cases (95.7%), rarely showed signs of infection (5.2%) at the time of presentation and hospitalisation was never required. CONCLUSIONS: Our study provides a detailed overview of patients admitted to an emergency department of a tertiary Swiss University Hospital after an animal or human bite. In summary, bite injuries are common among patients who present to the emergency department. Therefore, primary and emergency care clinicians should be familiar with these injuries and their treatment strategies. The high risk of infection, particularly in cat bites, may warrant surgical debridement in the initial treatment of these patients. Prophylactic antibiotic therapy and close follow-up examinations are recommended in most cases.